A technology of biologically valuable smoothies with the use of walnuts - Тюрікова, Інна Станіславівна; Пересічний, Михайло Іванович; Рогова, Наталія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The study suggests the possibility of using walnuts of milky-wax ripeness in the technology of smoothies. We have motivated the choice and conducted physical and chemical research of raw materials and semi-finished products based on them, as well as proved the compatibility of such ingredients as pumpkin, cherry plums and walnut additives. The organoleptic research proved the rational composition of smoothies: pumpkin – fresh/blanched or baked, cherry plums, and walnut additive – fresh walnuts/walnut extracts based on spirit or sugar. We have devised a pumpkin-based smoothie technology that uses biologically valuable walnut raw materials and determined that such smoothies have high consumer properties. We have proved the presence of antioxidant substances – vitamin C, b-carotene, as well as phenol and pectin substances – in the smoothies’ composition. The suggested technology allows obtaining new drinks with more bioactive substances that can be recommended in daily diet for people who practice healthy lifestyle. We view as promising further research in expanding the range of walnut-using beverages for recreational purposes.